Mobile coupons: what to offer, to whom, and where?. Issue 5 (11th May 2015) - Khajehzadeh, Saman; Oppewal, Harmen; Tojib, Dewi
Abstract : Purpose: – This paper aims to investigate the redemption of promotional offers in a mobile service context. It specifically studies how mobile coupon redemption depends on the type of product offered, the convenience of accessing a retailer and the consumer's shopping motivation. Retailers increasingly use mobile coupon services as a complementary channel to send promotional offers to consumers. Design/methodology/approach: – Two studies examine how the three factors interact in determining coupon redemption. Both involve a scenario-based experiment. Participants are over 750 members of an online panel in the USA. Findings: – The results show that when the retailer offers a hedonic product, consumers' shopping motivation matters more, whereas when the retailer offers a utilitarian product, consumers' location dominates their redemption intentions. Research limitations/implications: – One limitation of this research is the use of hypothetical scenarios. Although this limitation was addressed by conducting a quasi-experiment, future research could be carried out using a field experiment. Practical implications: – Results suggest that in a mobile channel, personalization of promotions is more important for utilitarian shoppers than for hedonic shoppers. Originality/value: – Drawing on the theories of regulatory focus and preference for the status quo, this paper posits that mobile coupon redemption is determined by whether the offer requires consumers to divert from their focal shopping motivation (i.e. their status quo). The authors explain this difference by showing the mediating role of regulatory fit.